Haemolymphatic cancer among children in Sardinia, Italy: 1974–2003 incidence. Issue 11 (3rd November 2020) - Broccia, Giorgio; Carter, Jonathan; Ozsin-Ozler, Cansu; Meloni, Federico; Pilia, Ilaria; Satta, Giannina; Murgia, Giulio; Campagna, Marcello; Cocco, Pierluigi
Abstract : Objectives: To explore the time trend and geographical distribution of childhood leukaemia incidence over the territory of the Italian region of Sardinia. Setting: All hospitals departments, diagnostic centres and social security agencies in Sardinia were regularly screened in 1974–2003 to identify, register and review the diagnoses of incident cases of haematological malignancies (HM). Participants: The whole child population aged 0–14 resident in Sardinia. Primary and secondary outcome measures: Incidence and time trend of childhood HM and childhood acute lymphoblastic leukaemia (ALL) over the study period, and use of Bayesian methods to plot the probability of areas with excess incidence on the regional map. Results: Overall, 675 HM cases, including 378 ALL cases, occurred among children aged 0–14 years resident in Sardinia in 1974–2003, with an incidence rate of 6.97×10 -5 (95% CI 6.47 to 7.51) and 3.85×10 -5 (95% CI 3.48 to 4.26), respectively. Incidence of HM and ALL showed an upward trend along the study period especially among females. Three communes out of the 356 existing in 1974, namely Ittiri, Villa San Pietro and Carbonia, stand out as areas with excess incidence of HM and ALL in particular and another, Carloforte, for ALL only. Conclusions: Our results might serve as convincing arguments for extending the coverage of routine cancer registration over the whole Sardinian population, while prompting further research on the genetic and environmental determinants in the areas at risk.